THE OLIGOCENE/MIOCENE BOUNDAR Y IN THE EQUATORIAL ATLANTIC DSDP SITE 354. RESULTS OF STUDIES ON PLANKTIC FORAMINIFERA AND CALCAREOUS NANNOFOSSILS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
A first order correlation between planktic foraminiferal and calcareous nannofossil events o( DSDP Site 354 in the Equatorial Atlantic is presented. Within the 323 m thick, discontinuously cored section, 30 sarnples have been studied. In the Oligocene-Miocene sedirnents 57 different species of planktic Foraminifera and 51 species of calcarcous nannofossils have been identified, and 6 foraminiferal zones and 7 nannofossil zones recognized. Besides the generally used biostratigraphic markers, some additional calcareous nannofossil events are considered for a further subdivision of the interval studied.
Keywords: Biostratigraphy; planktic Foraminifera; calcareous nannofossils; Oligocene/Miocene boundary; Equatorial Atlantic.